Современное состояние и перспективы развития лазерных методов обработки материалов - Коваленко, В.С. (Наука та наукознавство, 2006)
Освещены новые достижения в области лазерной техники и технологии, разработки НИИ лазерной техники и технологии НТУУ «КПИ», изложены концепции е-предприятия, позволяющего интегрировать научные и производственные ресурсы в данной области, национальной технологической платформы Украины. Приведены приоритеты, требующие особого внимания и поддержки, в области лазерной техники и технологии на ближайшие 3—5, 10—15 и 20—25 лет. Висвітлено нові досягнення у галузі лазерної техніки і технології, розробки НДІ лазерної техніки і технології НТТУ «КПІ», викладено концепції е-підприємства, яке дозволяє інтегрувати наукові та виробничі ресурси у даній галузі, національної технічної платформи України. Наведено пріоритети, потребуючі особливої уваги і підтримки, в галузі лазерної техніки і технології на найближчі 3—5, 10—15 та 20—25 років. The paper informs about the achievements in laser techniques and technologies, developments in laser techniques and technologies made in the Kiev Technical University “Kiev Politechnical Institute”, introduces the concepts of e-enterprise that allows to integrate R&D and production resources within one industry, the concept of the national technical platform of Ukraine. Priorities are emphasized in laser techniques and technologies, that require a particular focus and support in the forthcoming 3—5, 10—15 and 20—25 years.